2016
DOI: 10.1080/09273948.2016.1199712
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Glaucoma in a Cohort of Patients with Fuchs Heterochromic Iridocyclitis

Abstract: Risk factors for development of ocular hypertension/glaucoma were increasing patient age and having a cataract at presentation with FHC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…28 With regard to IOH/glaucoma, it has been suggested to occur in 15% to 59% of cases, consistent with our results. 9,20 Disease duration (i.e., time between onset of symptoms and diagnosis) was found to be positively associated with IOP values, suggesting that early diagnosis is of importance in the management of FHC.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…28 With regard to IOH/glaucoma, it has been suggested to occur in 15% to 59% of cases, consistent with our results. 9,20 Disease duration (i.e., time between onset of symptoms and diagnosis) was found to be positively associated with IOP values, suggesting that early diagnosis is of importance in the management of FHC.…”
Section: Discussionmentioning
confidence: 98%
“…Because of its mildly symptomatic nature and the possible atypical signs, diagnosis can be overlooked or delayed for years and even decades (Brancaleoni A, et al IOVS 2003;44:ARVO E-Abstract 2381), increasing the risk of developing sight-threatening complications. Toniolo et al 20 recently reported that 39% of FHC patients eventually develop intraocular hypertension (IOH) or glaucoma. 20 In this pathology, the severity of glaucoma resides in its poor responsiveness to maximal medical therapy but also to surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Optimal treatment, which can be complex and often includes both medical and surgical approaches, should be directed at the underlying cause(s) of OHT. Five original articles [14][15][16][17][18] 19 months -19 years) and the mean time from onset of uveitis to the diagnosis of uveitic glaucoma was 4.5 ± 4.9 years. A high proportion of affected eyes were exposed at some point to topical (73.6%), periocular (34.0%), and/or systemic (30.2%) corticosteroids.…”
mentioning
confidence: 99%